Pengaruh Pelatihan Keselamatan dan Kesehatan Kerja terhadap Perilaku Penggunaan APD pada Tenaga Kerja di Industri Konstruksi - Nabila Wafa Zahira; Andriyani Andriyani; Nurmalia Lusida (Inovasi Kesehatan Global, 2025)
Occupational safety and health training explains that increased knowledge and awareness of workers about potential workplace hazards can motivate them to comply with safety standards, including the use of personal protective equipment (PPE). This research aims to analyze the effect of occupational safety and health training on the behavior of using PPE by workers in the construction industry. This research is driven by the high number of work accidents that happen in the construction industry sector in Indonesia, where many workers are still reluctant to use PPE. The method used is a comprehensive literature review, with analysis of various relevant sources including academic journals and research reports as well as 3 electronic databases, namely Google Scholar, PubMed, and GARUDA. The findings of the study showed that workers who participated in occupational safety and health training showed increased knowledge and awareness of potential hazards in the workplace. Despite this, compliance rates are still low, especially among younger and less experienced workers. There is still no clear research data on reducing the accident rate in workers after this occupational safety and health training. This research confirms the need for strict supervision in the field to create a safer and healthier work environment.